The effectiveness of religion-based self-management training to reduce internet addiction in madrasah aliyah students - Hidayat Ma'ruf; Muafatin Muafatin (Universitas Negeri Padang, 2022)
Like a double-edged sword, the internet has many benefits but can also have negative impacts. The use of the internet in education can help improve student academic achievement, but its excessive use can make students addicted to the internet. Internet addiction can reduce academic achievement, reduce psycho-social abilities, and cause psycho-emotional problems. It is not easy and takes time to reduce internet addiction, because it has to wait for the individual to realize that he is experiencing a problematic behavior and wait for his will to change. Training self-management with a religious approach is seen as effective in reducing internet addiction for students who have religious lives. This study showed a significant decrease in internet addiction by 0.458 in students who took part in religious-based self-management training. Although the effectiveness is still low (N-Gain = 0.2) or N-Gain < 0.3, religion-based self-management training can raise awareness and willingness to change behavior and can significantly reduce internet addiction in all trainees.